2011
DOI: 10.1128/aac.00154-11
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Amodiaquine and Desethylamodiaquine in Pregnant and Postpartum Women with Plasmodium vivax Malaria

Abstract: In order to study the pharmacokinetic properties of amodiaquine and desethylamodiaquine during pregnancy, 24 pregnant women in the second and third trimesters of pregnancy and with Plasmodium vivax malaria were treated with amodiaquine (10 mg/kg of body weight/day) for 3 days. The same women were studied again at 3 months postpartum. Plasma was analyzed for amodiaquine and desethylamodiaquine by use of a liquid chromatography-tandem mass spectrometry method. Individual concentration-time data were evaluated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
42
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 27 publications
3
42
0
1
Order By: Relevance
“…This study was conducted in an area of low seasonal malaria transmission along the northwestern border of Thailand. Clinical details and noncompartmental analysis results are reported in full elsewhere (48). The study was carried out at weekly antenatal clinics at the Shoklo Malaria Research Unit (SMRU).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was conducted in an area of low seasonal malaria transmission along the northwestern border of Thailand. Clinical details and noncompartmental analysis results are reported in full elsewhere (48). The study was carried out at weekly antenatal clinics at the Shoklo Malaria Research Unit (SMRU).…”
Section: Methodsmentioning
confidence: 99%
“…However, CYP2C8 and CYP1A1 activities have not been reported to be altered during pregnancy (14). A noncompartmental analysis of amodiaquine and desethylamodiaquine reported no significant pharmacokinetic difference in pregnant women and postpartum women (48). Studies in pregnant women with malaria reported relatively unchanged pharmacokinetic properties of chloroquine and quinine (1,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This may contribute to lower antimalarial cure rates in pregnant than nonpregnant adults (58). Other studies report no pharmacokinetic differences in pregnant women compared to nonpregnant women (e.g., pyrimethamine and amodiaquine/desethylamodiaquine) or even a higher drug exposure during pregnancy (pyrimethamine) (15,25,46).…”
mentioning
confidence: 99%
“…This may contribute to lower antimalarial cure rates in pregnant than nonpregnant adults (58). Other studies report no pharmacokinetic differences in pregnant women compared to nonpregnant women (e.g., pyrimethamine and amodiaquine/desethylamodiaquine) or even a higher drug exposure during pregnancy (pyrimethamine) (15,25,46).Artemisinin-based combination therapy (ACT) is now recommended as first-line treatment for falciparum malaria in nearly all countries where malaria is endemic. ACTs are recommended by the World Health Organization in the second and third trimester of pregnancy (60).…”
mentioning
confidence: 99%